Relationship Between Metabolites of Vitamin D, Free 25-(OH)D, and Physical Performance in Indoor and Outdoor Athletes - Książek, Anna; Zagrodna, Aleksandra; Słowińska-Lisowska, Małgorzata; Lombardi, Giovanni (Frontiers in Physiology, 2022)
The potential effects of vitamin D in athletes has received considerable attention in the literature. However, little is known about vitamin D metabolites and its association with physical performance in athletes. Therefore, the aim of our study was to determine the relationship between metabolites of vitamin D, vitamin D binding protein (VDBP), free, bioavailable 25-(OH)D and physical fitness tests in athletes. A total of 40 indoor and outdoor players (16 judoists, 24 football players) participated in the study. Vitamin D metabolites (25-(OH)D, 24,25-(OH)2D3, 3-epi-25-(OH)D3, 1,25-(OH)2D) were assessed using LM-MS/MS). Free 25(OH)D concentration was evaluated by calculation, using serum albumin and vitamin D binding protein (VDBP) levels. Athletic performance was assessed using handgrip and vertical jump. Our study showed a significant correlation between vitamin D metabolites and handgrip strength and vertical jump variables in indoor players. It demonstrated a significant association between 3-epi-25(OH)D3 and vertical jump parameters in outdoor players. Results of our study showed relationship between free, bioavailable 25-(OH)D and vertical jump variables in indoor players. In conclusion, we provide novel information on the vitamin D metabolites and athletic performance in athletes. Based on results of our study, we concluded that vitamin D metabolites might be involved in skeletal muscle function in relation to athletic performance.